Waqf Land Management Problems and Solutions: A Case Study of the Regional Leaders of Muhammadiyah Tangerang Selatan - Maulina Wulandari; Saiful Anwar (Budapest International Research and Critics University, 2022)
The purpose of this study was to analyze the solution to the problem of waqf land management and to analyze the characteristics of nazir. This article uses a qualitative descriptive analysis research design. The data sources used are based on interviews with experts in the Waqf field and through library studies based on books, journals, internet, and other literature studies. The results in this study are information about land waqf in the community is still lacking, the weak management and supervision system for waqf land, both those that have been and those that have not been certified. The low level of competent human resources or nazir in the Muhammadiyah Regional Leadership, South Tangerang. The solution to the problem of waqf land is to provide guidance, training, and guidelines to nazir regarding the procedure for receiving land waqf, about using the SIMAM website (Muhammadiyah Asset Management Information System) to make it easier for wakif, and other communities to find out information about waqf owned by Muhammadiyah. Muhammadiyah Regional Leaders need to pay attention to the welfare of Nazir who works full time. The characteristics of nazir that must be possessed by the Muhammadiyah Regional Leadership in South Tangerang are nazir who is competent in the field of waqf, nazir who can work full time, is able to develop the SIMAM Website (Muhammadiyah Asset Management Information System), openness about waqf funds, develop waqf with a franchise business. Muhammadiyah Regional Leaders need to pay attention to the welfare of Nazir who works full time. The characteristics of nazir that must be possessed by the Muhammadiyah Regional Leadership in South Tangerang are nazir who is competent in the field of waqf, nazir who can work full time, is able to develop the SIMAM Website (Muhammadiyah Asset Management Information System), openness about waqf funds, develop waqf with a franchise business. Muhammadiyah Regional Leaders need to pay attention to the welfare of Nazir who works full time. The characteristics of nazir that must be possessed by the Muhammadiyah Regional Leadership in South Tangerang are nazir who is competent in the field of waqf, nazir who can work full time, is able to develop the SIMAM Website (Muhammadiyah Asset Management Information System), openness about waqf funds, develop waqf with a franchise business.